Nitration of primary amines to form primary nitramines (Review) - McAteer, Daniel; Pons, Jean-François; Wilson, Ian; Cavaye, Hamish (Cranfield University, 2016)
The nitration of primary amines to form primary nitramines is a rarely reported synthetic procedure which proceeds through a minimum of two steps. This is in stark contrast to the nitration of alcohols and secondary amines which is readily achievable by a number of methods in a single step. In general the primary amine must initially be activated to nitration as direct exposure to nitrating media tends to result in the formation of an ionic nitrate salt. This activation may be achieved through the use of a multitude of protecting groups that are stable to the nitrating conditions used thereafter. The review presented here is an attempt to bring together the published literature on this often overlooked synthetic procedure in energetic materials chemistry.
Poster presentation at 19th Seminar on New Trends in Research of Energetic Materials; Pardubice, Czech Republic; 20/04/2016-22/04/2016